ANALISIS PRODUKTIVITAS KERJA KARYAWAN DIKAITKAN DENGAN TIME MANAGEMENT - Elmira Febri Darmayanti (Akuisisi: Jurnal Akuntansi, 2016)
The increasing of society demand service of health will be more certifiable, effective, and reached these days oblige organizer of hospital to be more professional in conducting hospital management. The Apotek coordination with one of Installation Pharmacy under Governmental Hospital in West Java. Service factor placing human resource as an important element in it. Performance of Apotek’s employees determine satisfaction level of pharmacy services which is given to patient. So that, employees work productivity of the Apotek give an important contribution in pharmacy service system specially and service system of Hospital in general.The measurement method that used is work load, by using spot sampling method, which is representing work sampling pursuant to activity done at certain time dot and assumed to deputize an activity at that time dot. This method based on work characteristic, which are not chronological and requiring much time. Here in after analyzed about operating process as a whole, so that can be given alternatives for repairing process from time management. Its result indicate that entirely operation process at the Apotek will be able to influence employees performance. For that, after analysed we propose to repair the operation system.  Key Words : Productivity,Work Load, and Time Management.